Pengaruh K3 (Keselamatan dan Kesehatan Kerja) Terhadap Kinerja Karyawan SPBU COCO PLAJU 21.302.04 - Vanesha Rahmania; Okta Uliansyah; Riri Hanifa (Journal of Management, Entrepreneur and Cooperative, 2022)
ABSTRACT This study aims to examine the effect of K3 (Occupational Safety and Health) on employee performance at SPBU Coco Plaju 21.302.04 using SPSS. This stujdy uses the independent variable Occupational Safety and Health, Employee Performance the dependent variable. The method of data analysis in this study used quantitative data analysis, and used descriptive research. Primary data was collected using a questionnaire distributed to respondents. Data analysis in this final project information analysis method used in this research is multiple linear regression. Information processing in this research uses SPSS Statistics 20. The result show that safety has a positive and significant effect on employee performance. Occupational Health has a positive and significant effect of employee performance ata the Coco Plaju gas station 21.302.04.